2016
DOI: 10.1002/pro.2878
|View full text |Cite
|
Sign up to set email alerts
|

Using a second‐order differential model to fit data without baselines in protein isothermal chemical denaturation

Abstract: In vitro protein stability studies are commonly conducted via thermal or chemical denaturation/renaturation of protein. Conventional data analyses on the protein unfolding/(re)folding require well-defined pre-and post-transition baselines to evaluate Gibbs free-energy change associated with the protein unfolding/(re)folding. This evaluation becomes problematic when there is insufficient data for determining the pre-or post-transition baselines. In this study, fitting on such partial data obtained in protein ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…We also showed that commonly employed in silico methods cannot act as a surrogate for experimental measurements of flow‐induced aggregation propensity. We have previously shown that extensional flow triggers partial unfolding of BSA, 59 which may expose APRs that are sequestered from solvent in the thermodynamically stable native protein (Δ G UN = 15.2 kJ mol −1 ), 82 thereby evading detection by both CamSol and Solubis. In this regard, it is interesting to note that many of the APRs predicted by Solubis 26 are found on the V H ‐ V L interface or the CDRH3 loop (Figure S6b).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that commonly employed in silico methods cannot act as a surrogate for experimental measurements of flow‐induced aggregation propensity. We have previously shown that extensional flow triggers partial unfolding of BSA, 59 which may expose APRs that are sequestered from solvent in the thermodynamically stable native protein (Δ G UN = 15.2 kJ mol −1 ), 82 thereby evading detection by both CamSol and Solubis. In this regard, it is interesting to note that many of the APRs predicted by Solubis 26 are found on the V H ‐ V L interface or the CDRH3 loop (Figure S6b).…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic tryptophan fluorescence of PSMD10 Gankyrin was collected using PR.ChemControl software of Nanotemper Technologies to monitor chemical denaturation. We calculated the slopes of the pre‐transition and post‐transition data points and used the equations as described earlier to determine fraction unfolded 40 . The data points were further fitted using four parametric equations in Graphpad V8.0.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated the slopes of the pre-transition and post-transition data points and used the equations as described earlier to determine fraction unfolded. 40 The data points were further fitted using four parametric equations in Graphpad V8.0.…”
Section: Chemical Denaturationmentioning
confidence: 99%
“…The main controversial point of this method is the assumption that proteins are completely denatured under these experimental conditions, and such denaturation is completely reversible. However, a detailed analysis of the protocols of such experiments shows that most of the methods for assessing the unfolding of the protein structure are indirect and replete with numerous assumptions [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. Thus, proteins that are supposed as fully unfolded are actually only partially unfolded, and the degree and nature of unfolding of the same protein can differ significantly depending on the denaturation protocol used [ 104 , 107 ].…”
Section: Mechanisms Of the Formation Of Misfolded Proteinsmentioning
confidence: 99%